Doing cultural theory - Walton, David, 1955- (Sage, 2012)
"Doing Cultural Theory is a textbook and a toolkit that teaches the basics of cultural theory, unpacks its complexities with real-life examples, and shows readers how to link theory and practice. Offers accessible introductions to how cultural studies has engaged with key theories in structuralism, poststructuralism and postmodernism. Teaches straightforward ways of practicing these theories so students learn to think for themselves. Uses 'Practice' boxes to show students how to apply cultural theory in the real world. Guides students through the literature with carefully selected further reading recommendations Other textbooks only show how others have analyzed and interpreted the world. Doing Cultural Theory takes it a step further and teaches students step-by-step how to do cultural theory for themselves." -- Publisher's website.